Laparoscopic resection of giant endometriotic cysts with mesenteric implantation - Espitia, Francisco Terrazas; Dávila, David Molina; Álvarez, Jorge Fernández; Gallardo, Luis Miguel; Lugo, Pedro Brito; Ponton, Pablo Avila (International Surgery Journal, 2018)
ndometriosis is defined as the presence of tissue which is histologically similar to the endometrium in locations outside the uterus. It affects women of reproductive age mainly and represents one of the main causes for hysterectomy and infertility amongst women. It has a broad spectrum of symptoms which make for a challenging diagnosis. Extragenital endometriosis affects up to 37% of all patients, and intestinal endometriosis has been observed in up to 12% of women affected by the disease, mainly involving the recto-sigmoid colon, ileocecal region and cecal appendix. Intestinal symptoms such as changes in depositional rhythm, diarrhoea and constipation are frequent and can evolve to acute abdominal obstruction in advanced stages of the disease. Authors present the case of a 51-year-old female that presented to the emergency room with abdominal, colic type, diffuse pain in the left flank, early satiety and postprandial fullness, CT scan revealed the presence of a lobed and septate mesenteric cystic tumor, of approximately 15.5 cm in diameter. Serum oncological markers were found to be within normal parameters. The patient underwent laparoscopic resection of the tumor with trans-operatory study, which ruled malignancy out and confirmed the presence of endometriotic tissue. The patient was discharged 72 hrs after surgery and prescribed anastrozole 1 mg orally every 24 hours. Follow up with Abdominal CT scan was performed 6 and 18 months later, showing no evidence of recurrence; the patient remains asymptomatic 18 months after surgery.